Platelet function in patients with a history of unexplained recurrent miscarriage who subsequently miscarry again. (May 2015) - Dempsey, Mark Anthony; Flood, Karen; Burke, Naomi; Murray, Aoife; Cotter, Brian; Mullers, Sieglinde; Dicker, Patrick; Fletcher, Patricia; Geary, Michael; Kenny, Dermot; Malone, Fergal D.
Abstract: Objective: This study was designed to evaluate platelet aggregation in pregnant women with a history of unexplained recurrent miscarriage (RM) and to compare platelet function in such patients who go on to have either another subsequent miscarriage or a successful pregnancy. Study design: A prospective longitudinal study was performed to evaluate platelet function in a cohort of patients with a history of unexplained RM. Platelet reactivity testing was performed at 4–7 weeks gestation, to compare platelet aggregation between those with a subsequent miscarriage and those who had successful live birth outcomes. Platelet aggregation was calculated using a modified assay of light transmission aggregometry with multiple agonists at different concentrations. Results: In a cohort of 39 patients with a history of RM, 30 had a successful pregnancy outcome while nine had a subsequent miscarriage again. Women with subsequent miscarriage had reduced platelet aggregation in response to adenosine diphosphate ( P value 0.0012) and thrombin receptor activating peptide ( P value 0.0334) when compared to those with successful pregnancies. Women with subsequent miscarriages also had a trend towards reduced platelet aggregation in response to epinephrine ( P value 0.0568). Conclusion: Patients with a background history of unexplained RM demonstrate reduced platelet function if they have a subsequent miscarriage compared to those who go on to have a successful pregnancy.